Preparation and Characterization of Graphite-Epoxy Composite Modified with Zinc Hexacyanoferrate and Their Electrochemical Behaviour in Presence of Substituted Anilines - Fenga, Paula Goncalves [UNESP]; Stradiotto, Nelson Ramos [UNESP]; Isabel Pividori, Maria (Wiley-v C H Verlag Gmbh, 2010)
The growth of zinc hexacyanoferrate (ZnHCF) hybrid film on the surface of graphite-epoxy composite (GEC) electrodes was demonstrated by cyclic voltammetry. Surface morphology of the hybrid film was investigated by using scanning electron microscopy. The effect of the type of monovalent cations on the redox behaviour of hybrid film was also studied. This effect indicated that the radius of the hydrated cation mainly determines the ion permeability of the film.The electrochemical behavior of the substituted anilines (procaine and sulfamerazine) in 1 M KCl of the modified GEC electrode showed a decrease of the cathodic currents while increasing the concentration of these analytes. The developed sensor also showed excellent stability for long time usage, higher sensitivity and cost-effective fabrication.
Keywords: Graphite-epoxy composite electrode; Zinc hexacyanoferrate; Substituted anilines; Procaine; Sulfa drugs; Sulfamerazine